Implementasi Pembelajaran Berdiferensiasi dalam Pemenuhan Kebutuhan Belajar Peserta Didik di Sekolah Dasar - Fitri Indriani, Fitri Indriani; Prabaningtyas, Amyseza; Kurniasari, Candra (azkiya, 2024)
This research aims to analyze the implementation of differentiated learning in meeting students' learning needs in elementary schools. The research method is descriptive qualitative with the research subjects, namely class II B students with a total of 29 students in Mathematics subjects on time material. Data collection techniques using observation, interviews and documentation techniques. The data validity test was carried out by triangulating techniques and sources. Data analysis techniques by collecting data, data reduction, data presentation and conclusion drawing. The results showed that the implementation of differentiated learning in meeting student learning needs by implementing differentiated learning strategies of content, process, product and environment. The supporting factors for differentiated learning are the mapping of students and adequate facilities so that they can facilitate the interests, needs and learning styles of students. While the inhibiting factors require more intensive time and preparation for teachers, active class conditions so that it takes time to condition the class to be conducive, and different expectations between teachers and students in understanding the material can be one of the obstacles..